Improving physical activity and metabolic syndrome indicators in women: A transtheoretical model-based intervention - Firoozeh Mostafavi; Fazllolah Ghofranipour; Awat Feizi; Asiyeh Pirzadeh (International Journal of Preventive Medicine, 2015)
Background: This study aimed at investigating the impact of an educational intervention based on transtheoretical model to increase physical activity and improve metabolic syndrome indicators in women. Methods: In this quasi-experimental study, 142 women with metabolic syndrome were randomly assigned to the case and control group (each group 71 participants). SECQ (Marcus), processes of change (Marcus), decisional balance (Bandura) and self-efficacy (Nigg) questionnaires and International Physical Activities Standard Questionnaire in preintervention, 3 and 6 months after intervention were completed. Furthermore, abdominal obesity, triglycerides (TG), and high-density lipoprotein (HDL) were measured. Physical activity intervention based on transtheoretical model (TTM) was performed in the case group. Finally, data were analyzed by SPSS (16) (SPSS Inc., Chicago, IL, USA) and repeated measure ANOVA, independent t-test and Freidman was used. A two-tailed P value, lower than 0.05, was considered to be statistically significant. Results: After the intervention, physical activity level increased in the intervention group, and they also progressed in stages of change, but the people in the control group had regressed. All changes in TTM constructs were significant in the intervention group during the time and differences in pros and cons were not significant in the control group. Abdominal obesity and TG has significantly reduced, and HDL has increased in the intervention group. In the control group, there was a significant increase in TGs and a decrease in HDL. Conclusions: Physical activity training based on TTM can improve physical activity and metabolic syndrome indicators in women.